Inspiratory muscle activation during inspiratory muscle training in patients with COPD. (December 2021) - Lee, Chien-Tzu; Chien, Jung-Yien; Hsu, Miao-Ju; Wu, Huey-Dong; Wang, Li-Ying
Abstract: Background and objectives: The main target of inspiratory muscle training (IMT) is to improve diaphragm function in patients with COPD who have inspiratory muscle weakness. Ventilatory demand is already increased during quiet breathing in patients with COPD, and whether threshold load imposed by IMT would active more accessory muscle remained to be determined. The purpose of this study was to examine diaphragm and sternocleidomastoid (SCM) activation during IMT with intensities of 30% and 50% maximal inspiratory pressure (PImax ). Methods: Patients with COPD and a PImax lower than 60 cmH2 O were recruited for the study. Surface electromyography (EMG) was used to measure diaphragm and SCM activation, and group-based trajectory modeling (GBTM) was used to identify activation patterns during IMT. The generalized estimating equation (GEE) was then used to detect differences of variables between various breathing tasks. Statistical significance was established at p  < 0.05. Results: A total of 30 patients with COPD participated in this study. All patients demonstrated significant increases in diaphragm and SCM activation during 30% and 50% PImax of IMT than during quiet breathing (all p  < 0.001). Diaphragm demonstrated two distinct patterns in response to IMT: low activation (n = 8) and high activation (n = 22) group using GBTM analysis. Conclusion: Diaphragm and SCM were substantially activated during IMT in patients with COPD who had inspiratory muscle weakness. Regardless of whether diaphragm activation was high or low, SCM was activated to a greater extent in response to IMT. Highlights: Diaphragm and SCM were substantially activated during IMT in patients with COPD. Two distinct activation patterns of diaphragm were identified in response to IMT. Despite the level of diaphragm activation, SCM was activated considerably during IMT.